Die Wirkung der Hartz-Reform im Bereich der beruflichen Weiterbildung - Hilmar Schneider; Arne Uhlendorff (Institute for the Study of Labor (IZA), 2006)
The so-called Hartz reform has introduced fundamental changes for publicly sponsored training in Germany. This concerns primarily the emission of training vouchers as an exclusive allocation device, allowing potential participants free choice among training providers within a given training target range. In addition, delivery of training vouchers is conditioned on sufficient re-employment prospects of a job-seeker. We comparatively examine the impact of participation for the quantitatively most important type of training programs before and after the reform by using administrative data of the Federal Employment Agency. Based on conditional propensity score matching, we investigate average treatment effects by means of non-parametrically estimated state probabilities and semi-parametrically estimated transition rates. Our results show that participation in training programs had a positive impact on employment prospects already before the reform. Results for the relative short observation period since the reform are pointing to a further increase of effectiveness. The driving force behind this seems to come from reducing the duration of training programs, which has decreased the lock-in effect without affecting the program effect.
Keywords: J64; J68; H43; 330; program evaluation; occupational training; Hartz-Reforms; Germany; Arbeitsmarktpolitik; Reform; Hartz-Reform; Weiterbildung; Arbeitslosigkeit; Berufliche Integration; Deutschland